Ibn Ashur’s Grammatical Preferences and their Impact on Meaning in his Tafsir al-Tahrir wa al-Tanwir Selected Examples from Surah al-Kahf - Maryoumah Abdulhadi Abdullh Iftees (Journal of Scientific and Human Dimensions, 2026)
This research examines the grammatical preferences of Imam Ibn Ashur in his exegesis "Al-Tahrir wa al-Tanwir," through selected examples from Surah Al-Kahf. It aims to reveal the impact of these preferences on guiding the Quranic meaning. The research employs a descriptive-analytical approach, reviewing several verses where grammatical disagreement exists, such as the interpretation of "wa la yaj’al lahu ’ujajan" (the conjunction "wa" is either parenthetical or circumstantial), "qayyiman" (circumstantial or an implied object), "ahsa" (comparative or past tense verb), "wa thamanhum" (the conjunction "wa" is used for the eighth), the issue of exception in verse 23, and others. The research demonstrates how Ibn Ashur does not merely present grammatical possibilities, but rather favors the interpretation that achieves a deeper meaning, thus connecting grammar with meaning and rhetoric, such as negating any crookedness in the Book, emphasizing the threat, or affirming ownership and exclusivity. Among the most prominent findings is that Ibn Ashur rejects the so-called "waw of eight," considering it a myth, and he avoids unnecessary grammatical embellishments. The research recommends comparative studies between Ibn Ashur’s interpretation and others, as well as an analysis of the rhetorical devices in "Al-Tahrir wa al-Tanwir.".